1992
DOI: 10.1037/0096-3445.121.2.210
|View full text |Cite
|
Sign up to set email alerts
|

Visual experience, visual field size, and the development of nonvisual sensitivity to the spatial structure of outdoor neighborhoods explored by walking.

Abstract: When places are explored without vision, observers go from temporally sequenced, circuitous inputs available along walks to knowledge of spatial structure (i.e., straight-line distances and directions characterizing the simultaneous arrangement of the objects passed along the way). Studies show that a life history of vision helps develop nonvisual sensitivity, but they are unspecific on the formative experiences or the underlying processes. This study compared judgments of straight-line distances and direction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
1
4

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 44 publications
2
65
1
4
Order By: Relevance
“…In a comparison of congenitally and adventitiously blind children on a task involving pointing to known locations while traveling over a known route, Dodds, Howarth, and Carter (1982) found that some of the congenitally blind children performed extremely poorly. In another study involving large-scale space, Rieser, Hill, Talor, Bradfield, and Rosen (1992) found that both congenitally blind subjects and those who had suffered large-field losses early in life exhibited poorer knowledge of the spatial disposition of landmarks within their communities than the other subject groups (sighted, adventitiously blind, and those suffering early acuity loss but not large-field loss). Similarly, Casey (1978) found that the congenitally blind were less accurate in creating tactual maps of their school campus than those blinded later in life.…”
Section: Role Of Visual Experience In Navigation Abilitymentioning
confidence: 99%
“…In a comparison of congenitally and adventitiously blind children on a task involving pointing to known locations while traveling over a known route, Dodds, Howarth, and Carter (1982) found that some of the congenitally blind children performed extremely poorly. In another study involving large-scale space, Rieser, Hill, Talor, Bradfield, and Rosen (1992) found that both congenitally blind subjects and those who had suffered large-field losses early in life exhibited poorer knowledge of the spatial disposition of landmarks within their communities than the other subject groups (sighted, adventitiously blind, and those suffering early acuity loss but not large-field loss). Similarly, Casey (1978) found that the congenitally blind were less accurate in creating tactual maps of their school campus than those blinded later in life.…”
Section: Role Of Visual Experience In Navigation Abilitymentioning
confidence: 99%
“…We did not have sufficient information on visual-field status to compute correlations, but previous studies indicate that visual field loss is associated with increased errors in obstacle avoidance (Turano, et al, 2004). Field loss from eye disease (Rieser, Hill, Talor, Bradfield, & Rosen, 1992) or artificial restriction (Mason, 2002) also results in decreased wayfinding performance. …”
mentioning
confidence: 99%
“…The present study examined the abilities of adult blind observers who regularly use well-developed travel skills. Lockman et al (1981) and Rieser et al, (1992) provide direct empirical support for the importance of the role of travel skill where such skill was more varied in the subject populations studied. Loomis et al (in press) also report data from several navigation tasks, in which no differences were found between blind and sighted subjects.…”
Section: Comparability Of the Sighted To The Blindmentioning
confidence: 99%